Incidencia de la participación ciudadana en los procesos de gestión social de la parroquia urbana Ochoa León - pasaje 2023. - Chuchuca Ajila, Christopher Sleiter; Marin Mosquera, Angel Roberto (Machala, 2024)
The present work focuses on the study of the incidence of citizen participation in the social management processes of the urban parish of Ochoa León, as well as the types of mechanisms implemented, the contribution of the P.C in the social management of neighborhood organizations and the different spaces for citizens to intervene and get involved in social and political aspects. and in the full and direct exercise to exert influence in decision-making, conflict resolution and satisfaction of needs from the Ochoa León parish, given that a large part of the neighborhood councils are inactive, making it difficult to solve the problems of the sectors or neighborhoods, in addition to the scant attention of the Municipal GAD in providing institutionally the instruments and mechanisms to generate a sense of belonging and empowerment. In this way, the general objective has been proposed: To establish the incidence of citizen participation in the social management processes of the urban parish of Ochoa León – Pasaje, in addition to the specific objectives: To identify the types of participation mechanisms that have been implemented in the urban parish of Ochoa León; To determine the contribution of citizen participation in the social management of neighborhood organizations in the urban parish of Ochoa León and to distinguish the spaces of citizen participation in the urban parish of Ochoa León, in this way they direct the achievements that will be achieved in the research. The research is supported by theoretical information from articles, books and scientific journals of the last 5 years to provide credibility and viability, also the sociological foundation is the functionalist structural theory to understand the representation of citizens in the different, groups, collectives, organizations, communities and neighborhood councils through the participation in the demonstration to the competent authorities on the fulfillment of rights, solve their problems and solve their needs. The research methodology is empirically inductive and a rational deductive approach, on the other hand, it maintains a basic research since it provides knowledge about a theoretical foundation, also the investigated variables will provide an understanding of the problem through an analysis without the manipulation of these. On the other hand, an inductive method is applied, which allows to expand the knowledge obtained from particular facts to have a more general and deductive vision for the premises that are true to obtain a validated conclusion. The results of the research through the technique of survey, interview and observation guide have allowed us to identify that the mechanisms of social control according to 36.57% have not participated in any of them, while the spaces of citizen participation 40.10% manifest none, likewise in relation to the level of management of neighborhood organizations, 52.97% mention a low level, deducing that limited citizen participation and disorganization is the reason for the lack of participation in the management of neighborhood organizations. The cornerstone of neighborhood boards, committees and directives, in short, do not contribute to achieving social cohesion among the inhabitants that allow social problems, conflicts and needs to be resolved.
El presente trabajo se enfoca en el estudio de la incidencia de la participación ciudadana en los procesos de gestión social de la parroquia urbana Ochoa León, así mismo los tipos de mecanismos implementados, la contribución de la P.C en la gestión social de las organizaciones barriales y los diferentes espacios para que la ciudadanía pueda intervenir e involucrarse en los aspectos sociales y políticos, y en el ejercicio pleno y directo para ejercer influencia en la toma de decisiones, resolución de conflictos y satisfacción de las necesidades desde la parroquia Ochoa León, dado que, gran parte de los consejos barriales se encuentran inactivos, dificultando en esta medida el resolver los problemas de los sectores o barrios, además de la escasa atención del GAD Municipal en brindar de forma institucional los instrumentos y mecanismos para generar un sentido de pertenencia y empoderamiento. De esta manera se ha planteado el objetivo general Establecer la incidencia de la participación ciudadana en los procesos de gestión social de la parroquia urbana Ochoa León – Pasaje, además de los objetivos específicos: Identificar los tipos de mecanismo de participación se han implementado en la parroquia urbana Ochoa León; Determinar la contribución de la participación ciudadana en la gestión social de las organizaciones barriales de la parroquia urbana Ochoa León y Distinguir los espacios de participación ciudadana en la parroquia urbana Ochoa León, de esta manera direccionan lo logros que se van alcanzar en la investigación La investigación se sustenta con información teórica de artículos, libros y revistas científicas de los último 5 años para brindar credibilidad y viabilidad, así mismo la fundamentación sociológica es la teoría estructural funcionalista para comprender la representación de la ciudadanía en las diferentes, agrupaciones, colectivos, organizaciones, comunidades y consejos barriales a través de la participación en la manifestación a las autoridades competentes sobre el cumplimiento de derechos, resuelvan sus problemas y solucionen sus necesidades. La metodología de la investigación es empírico inductivo y un enfoque racional deductivo, por otro lado, mantiene una investigación básica dado que aporta conocimientos acerca de una fundamentación teórica, así mismo las variables investigadas brindaran un entendimiento del problema a través de un análisis sin la manipulación de estas. Por otro lado, se aplica un método inductivo por lo que permite ampliar el conocimiento que se obtiene de hechos particulares para tener un visón más general y deductivo por las premisas que son verdaderas para obtener una conclusión validada. Los resultados de la investigación a través de la técnica de la encuesta, entrevista y guía de observación han permitido identificar que los mecanismos de control social según el 36,57% no ha participado de ninguno, mientras que los espacios de participación ciudadana el 40,10% manifiestan ninguno, así mismo en relación al nivel de gestión de las organizaciones barriales el 52,97% mencionan un nivel bajo deduciendo que la limitada participación ciudadana y la desorganización es la piedra angular de los directorios, comités y directivas barriales, en definitiva, no contribuyen a lograr una cohesión social en los habitantes que permitan resolver los problemas sociales, conflictos y necesidades.
Keywords: PARTICIPACION CIUDADANA; GESTION SOCIAL; ORGANIZACION BARRIAL